Evaluation of the tolerability and effectiveness of Tenecteplase in patients with ST-Segment-Elevation Myocardial Infarction in a Secondary Hospital in Malaysia: A Retrospective Case Series - Kin Wei Chua, MSc,Med (ClinEpi); Sreevali Muthuvadivelu, BSc (Hons); Rosilawati Abdul Rani, MPH; Siew Chin Ong, PhD; Narwani Hussin, MCM; Wee Kooi Cheah, FRCP (London) (Elsevier, 2021)
ABSTRACT: Background: In Malaysia, knowledge regarding the clinical efficacy of tenecteplase (TNK), a fibrin-specific tissue-plasminogen activator, is limited. Objectives: To evaluate the effectiveness and tolerability of TNK in patients with ST-segment-elevation myocardial infarction in a secondary referral Malaysian hospital. Methods: This was a single-center retrospective case series based on the medical records of patients with ST-segment-elevation myocardial infarction admitted to the cardiac care unit between January 2016 and May 2019. Data regarding the mortality status and date of death were collected from the database of the National Registration Department of Malaysia. Results: Data for 30 patients with ST-segment-elevation myocardial infarction, who received weight-adjusted doses of TNK, were analyzed. The patients' mean (SD) age was 62 (14) years, and 77% were men. The median time to treatment was 265 minutes (interquartile range = 228-660 minutes), and the clinical success rate of thrombolysis was 79%. The overall all-cause in-hospital mortality rate was 33%. The 1-year survival rates were higher in patients achieving a time to treatment ≤360 minutes (P = 0.03), with a trend toward greater survival in this group at 30 days. Similarly, a trend toward lower in-hospital all-cause mortality was observed in this group (21% vs 50%; P = 0.12). Only 1 patient (3%), who had a HAS-BLED score based on hypertension, abnormal liver/renal function, stroke history, bleeding history or predisposition, labile international normalized ratio, old age, drug/alcohol use of 5, developed major bleeding that required blood transfusion. No cases of ischemic stroke, nonmajor bleeding, in-hospital reinfarction, or TNK-induced allergic reaction were identified. Conclusions: We hypothesized that the mortality-related outcomes of TNK in patients with ST-segment-elevation myocardial infarction were influenced by TTT, with TTT ≤360 minutes indicating a better prognosis than TTT >360 minutes. TNK-induced bleeding-related complications were minimal in low-risk patients. Further local studies are needed to compare TNK's profile with that of streptokinase, which is a common agent currently used in clinical practice in Malaysian public hospitals. (Curr Ther Res Clin Exp. 2021; 82:XXX-XXX)